2000
DOI: 10.1152/ajpcell.2000.278.1.c17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid entry of bitter and sweet tastants into liposomes and taste cells: implications for signal transduction

Abstract: Some amphipathic bitter tastants and non-sugar sweeteners are direct activators of G proteins and stimulate transduction pathways in cells not related to taste. We demonstrate that the amphipathic bitter tastants quinine and cyclo(Leu-Trp) and the non-sugar sweetener saccharin translocate rapidly through multilamellar liposomes. Furthermore, when rat circumvallate (CV) taste buds were incubated with the above tastants for 30 s, their intracellular concentrations increased by 3.5- to 7-fold relative to their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…Fourth, there may be a nonspecific mechanism for FFA detection, such as passive diffusion across taste cell membranes and activation of intracellular signaling systems. Detection of lipophilic sweet and bitter compounds has been documented by this mechanism (DeSimone 2000; Peri et al 2000;Zubare-Samuelov et al 2005). The amphipathic property of FFAs allows them to rapidly translocate across membranes (Hamilton and Kamp 1999;Hamilton et al 2001;Kamp and Hamilton 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, there may be a nonspecific mechanism for FFA detection, such as passive diffusion across taste cell membranes and activation of intracellular signaling systems. Detection of lipophilic sweet and bitter compounds has been documented by this mechanism (DeSimone 2000; Peri et al 2000;Zubare-Samuelov et al 2005). The amphipathic property of FFAs allows them to rapidly translocate across membranes (Hamilton and Kamp 1999;Hamilton et al 2001;Kamp and Hamilton 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, if there are other unidentified receptor systems or if detection is based on nonspecific mechanisms, such as FFA diffusion across taste cell membranes with subsequent activation of intracellular signaling systems, there may be no regional differences. Evidence for the latter mechanism has been provided for sodium chloride (NaCl) and acids where Na and protons pass through ion channels (DeSimone and Lyall 2006) as well as selected sweet and bitter stimuli capable of diffusing through the taste cell membranes (DeSimone 2000; Peri et al 2000;ZubareSamuelov et al 2005). Threshold and suprathreshold responses to FFAs varying in chain length were obtained from different tongue regions to test these hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple bitter receptors are expressed in a taste receptor cell, but bitter receptors and sweet receptors are rarely present in the same cell type. Although the studies we describe below concentrate on this family of receptors, a second path for bitter perception may exist that is independent of the receptors and their G-proteins [60,61]. This second pathway is open to those bitter chemicals that can come into the cell directly (because some bitter compounds are both water and lipid-loving and can permeate into the taste receptor cell).…”
Section: Location and Receptorsmentioning
confidence: 99%
“…This shift has been explained by the activation at low concentrations of sweet tastant-sensing G protein-coupled receptors (GPCRs) T1R2/ T1R3 (23) and at higher concentrations, the activation of the bitter tastant sensing GPCRs, T2R43, and T2R44 for saccharin and acesulfame-K (21). Other taste sensations related to the aftertaste elicited by artificial sweeteners have been attributed to their diffusion into taste receptor cells where they can alter intracellular signaling pathways (37,38,40,57). A recent psychophysical study showed that it is sometimes difficult to distinguish between the bitterness caused by quinine and the irritating sensation produced by capsaicin, the principal pungent ingredient in chili peppers that activates TRPV1 receptors (24).…”
mentioning
confidence: 99%
“…Peptide toxins from tarantula venom also activate TRPV1 receptors (45). As the capsaicin binding site is on the cytoplasmic surface of TRPV1 (17,18), all of these organic molecules must either be synthesized intracellularly or be able to permeate into the lingual epithelia, where they could diffuse into TRCs (40,57,58) or nerve terminals (4,15) and eventually activate TRPV1 receptors. TRPV1 receptors have also been shown to be directly activated on the extracellular side by high concentrations of Ca 2ϩ and Mg 2ϩ (1).…”
mentioning
confidence: 99%